Does Bright Light Counteract the Post-lunch Dip in Subjective States and Cognitive Performance Among Undergraduate Students? - Zhou, Ying; Chen, Qingwei; Luo, Xue; Li, Le; Ru, Taotao; Zhou, Guofu (Frontiers in Public Health, 2021)
The post-lunch dip in alertness and performance was widely experienced during the early afternoon. Taking a short nap was documented as a practical strategy for habitual nappers to counteract the decline of alertness and performance. Yet, it remains unknown whether bright light exposure in the early afternoon working hours could alleviate the performance deficits caused by a post-lunch nap loss for habitual nappers. Seventeen undergraduate students who had a long-term habit of taking a post-lunch nap were assigned to three interventions: (1) a short nap + normal indoor light (100 lx, 4,000 K at eye level); (2) no nap + normal indoor light, and (3) no nap + blue-enriched bright light (1,000 lx, 6,500 K at eye level), in which subjective alertness (Karolinska Sleepiness Scale, KSS), mood (Positive and Negative Affect Schedule, PANAS), and task performance in sustained attention (psychomotor vigilance test, PVT), response inhibition (go/no-go task), and working memory (paced visual serial addition test, PVSAT) were measured. Results showed that a post-lunch nap deprivation significantly increased subjective sleepiness and negative mood and impaired performance in PVT and PVSAT, while exposure to bright blue-enriched white light vs. normal indoor light in the early afternoon significantly relieved such negative effects on mood, sleepiness, and performance in PVSAT; subjective positive mood and performance in PVT and go/no-go task remained unaffected with light intervention. These findings suggested that bright blue-enriched white light exposure could be a potential strategy for those who are suffering from drowsiness and low working memory following a habitual midday nap loss.